AWARENESS OF VALUE EDUCATION BY SOCIAL STUDIES STUDENTS AND ACTUALIZING THE SUSTAINABLE DEVELOPMENT GOALS - Esther Uche Obiajulu-Anyia (Social Sciences and Education Research Review)
Actualizing the Sustainable Development Goals in many countries have been met with many challenges and problems, hence this study is an attempt to examine Social Studies students awareness level of value education and then relate it with achieving the Sustainable Development Goals. Five hypotheses were formulated and tested at 0.05level of significance. Correlational Research Design was used for the study. A sample size of 880 Basic 8 students from 36 secondary schools were drawn from a population of 48.095 Basic 8 students in Edo and Delta states in Nigeria. Purposive and random sampling techniques were used to sample the schools and respondents respectively. The instrument of data collection was a researcher's constructed and validated questionnaire titled "Students Awareness of Value Education and Actualizing the Sustainable Development Goals Questionnaire" (SAVEASDGQ). The reliability of the instrument was established with Cronbach-alpha reliability technique, with a reliability coefficient index of 0.75. After the collection of data, Pearson's Product Moment Correlation (PPMC) was used to test all hypotheses at 0.05 level of significance. The following results/findings were reported, there was significant relationship between awareness of value education on the one hand and "clean water and sanitation"; "responsible consumption and production"; "decent work and economic growth"; "sustainable cities and communities" and "affordable clean energy" on the other hand. Following these findings, the researcher recommended that value education should be adopted as a powerful tool for empowering young Nigerians at the Basic School level, on cultivating environmental friendly and responsible values, behaviours and attitudes towards the environment as this can assist in achieving the Sustainable Development Goals (SDGs).